An Endoskeleton Framework Biped Robot, "ADDAM" with Coupled Link Mechanism - Lee, Yong-Kwun; Lim, Dong-Won (KOREAN SOC PRECISION ENG, 2011)
This paper describes an endoskeleton anthropomorphic biped robot design and construction. The endoskeleton structure is aimed for robot's high power efficiency over its weight, but it demands unique structure and devices of the robot coping with the complexity. The gadgets newly developed for the robot such as a linear actuator, coupled link mechanism, inertia and Zero Moment Point(ZMP) sensors are described. The corresponding design procedure inevitably becomes sophisticated, so the powerful design tool to deal with this difficulty is utilized, and the way is explained. Feedback control scheme was established for its stable walking. Based on the outcome of the design, analysis, and simulation data, the actual robot was constructed and the paper shows its successful experimental results.